Multiple facets of biodiversity drive the diversity–stability relationship - John Griffin (Nature Ecology & Evolution, 2018)
A substantial body of evidence has demonstrated that biodiversity stabilizes ecosystem functioning over time in grasslandecosystems. However, the relative importance of different facets of biodiversity underlying the diversity–stability relationshipremains unclear. Here we use data from 39 grassland biodiversity experiments and structural equation modelling to investigatethe roles of species richness, phylogenetic diversity and both the diversity and community-weighted mean of functionaltraits representing the ‘fast–slow’ leaf economics spectrum in driving the diversity–stability relationship. We found that highspecies richness and phylogenetic diversity stabilize biomass production via enhanced asynchrony in the performance ofco-occurring species. Contrary to expectations, low phylogenetic diversity enhances ecosystem stability directly, albeit weakly.While the diversity of fast–slow functional traits has a weak effect on ecosystem stability, communities dominated by slowspecies enhance ecosystem stability by increasing mean biomass production relative to the standard deviation of biomass overtime. Our in-depth, integrative assessment of factors influencing the diversity–stability relationship demonstrates a more multicausalrelationship than has been previously acknowledged.